2008
DOI: 10.1002/mc.20431
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signatures that classify the mode of invasion of primary oral squamous cell carcinomas

Abstract: To identify molecular signatures and establish a new diagnostic model for progressive oral squamous cell carcinoma (OSCC). Total RNAs were isolated from primary OSCCs from both node-positive and -negative patients and used in cDNA microarray analysis. To identify marker genes representing a malignant phenotype, their expression was further examined by quantitative reverse transcription-PCR (QRT-PCR) in 64 OSCC tissues. Using Fisher's linear discriminant analysis (LDA) fitted with a stepwise increment method, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Our CLSP immunostaining results are in agreement with previously reported down-regulation of CLSP in advanced OSCC [12] and under-expression of CLSP in cervical cancer [40,41] but contrast with over-expression of CLSP in invasive and metastatic breast cancer [42]. A direct role for CLSP in carcinogenesis is countered by reports that transient transfection of CLSP into immortalized human keratinocytes and cervical cancer cell lines did not influence cell phenotype [40].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our CLSP immunostaining results are in agreement with previously reported down-regulation of CLSP in advanced OSCC [12] and under-expression of CLSP in cervical cancer [40,41] but contrast with over-expression of CLSP in invasive and metastatic breast cancer [42]. A direct role for CLSP in carcinogenesis is countered by reports that transient transfection of CLSP into immortalized human keratinocytes and cervical cancer cell lines did not influence cell phenotype [40].…”
Section: Discussionsupporting
confidence: 94%
“…Expression of CLSP is up-regulated in oral leukoplakia [8] and PMOLs [6], but down-regulated in advanced OSCC [12]. ELF3 is a member of ETS (E26 transformation-specific) family of transcription factors which is induced during keratinocyte differentiation in normal epithelia [13] and has been shown to be down-regulated in PMOLs [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…Next, comprehensive gene expression was compared between Sq-1979 and L cells to identify differentially expressed mRNAs. Our previous studies demonstrated that the expression of certain mRNAs, such as keratin1 and transglutaminase 3, exhibit continual changes from pre-cancerous to cancerous tissues and to further malignant OSCCs (4,9). In the present study, it was revealed that the expression of certain marker mRNAs could be an index for evaluating the histological grading of precancerous and OSCC tissues obtained from patients.…”
Section: Introductionmentioning
confidence: 47%
“…cDNA samples from 18 patients with OSCC (median age, 65 years; 7 male, 11 female; age range, 38-91 years) and 18 patients with LP (median age, 72 years; age range, 57-98 years) were incorporated into the present study. Tissue samples that had been surgically resected in the Dental Hospital of Hokkaido University (Sapporo, Hokkaido, Japan) between February 1998 and April 2004, and cDNA synthesis had already been performed, as described previously (9). All procedures were undertaken after written informed consent had been obtained from each patient, and the study adhered to the ethical guidelines of the dental hospital of the Hokkaido University School of Dentistry (Sapporo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation